Student trends towards football activity during the physical education and sports lesson Secondary level - bouhadj mezyane (sports creativity, 2025)
Physical education and sports are considered one of the forms of academic subjects such as natural sciences, chemistry and language, but they differ from these subjects in that they provide students not only with motor skills and experiences, but also provide them with a lot of knowledge and information that deals with health, psychological and social aspects, in addition to information that deals with scientific aspects such as the formation of the human body. This discussion calls us to study motivations, which are among the most important topics in psychology. To achieve this study, a sample of students aged 16-18 years in secondary school in the state of Sidi Bel Abbes, numbering around 100 students, was selected. The descriptive approach was used in its survey method, where we used percentages in analyzing the results to study the motivations of students' inclinations towards football activity during physical education and sports class. Based on this study, I arrived at a field fact that students are inclined towards football activity, and this is due to real motives, including internal motives, the most prominent of which are enjoyment, comfort, and entertainment, and external motives, the most prominent of which are the achievements of the national team, the development of sports facilities, especially football stadiums, and the development of global football. This is what the research results showed.